Everything you always wanted to know about sex and Neurology: neurological disability and sexuality - Alejandro Nasimbera; Julieta Rosales; Berenice Silva; Ricardo Alonso; Natalia Bohorquez; Sandra Lepera; Nelida Garretto; Tomoko Arakaki; Orlando Garcea; Raul Rey; Cecilia Quarracino; Gabriel E. Rodriguez (Arquivos de Neuro-Psiquiatria)
ABSTRACT Chronic neurological disorders generate disabilities affecting multiple aspects of life, including sexuality. Objective To describe the presence of sexual dysfunction and comorbidities in a population with chronic neurological disorders. To analyze the relationship between disability and sexual dysfunction. Methods A cross-sectional case-control study was carried out. Patients with amyotrophic lateral sclerosis (ALS), multiple sclerosis (MS), Parkinson’s disease (PD), and stroke of at least one year since the onset of symptoms were included, and compared with controls with no neurological disease, matched by age and sex. Results We included 71 participants: 29 controls, with a mean age of 49.4 years, and 42 patients with a mean age of 53.8 years. Sexual dysfunction was present in 22.5% of the controls and 77.5% of the patients. A statistically significant relationship between sexual dysfunction and disability was found in the logistic regression analysis (OR = 20.38, 95%CI: 2.5 –165.86). Conclusions Disability proved to be the main variable related to the presence of sexual dysfunction. Patients with ALS had the worst rates of sexual dysfunction. Patients with MS were similar to the control group. As for the PD group, no patient had normal sexuality. Finally, in stroke patients, the presence of comorbidities and their treatment may have negatively influenced sexuality. These findings showed that patients with chronic neurological diseases have sexual dysfunction and underscore the need for neurologists to know and address this problem.